Perancangan Aplikasi Digital Kultur sebagai Ruang Pamer Berbasis 3D Website untuk Karya Seni Rupa - Ranti Rachmawanti; Djarlis Gunawan; Cucu Retno Yuningsih (JURNAL RUPA, 2022)
This article discusses the design of the Digital Kultur application to become a virtual exhibition space for works of art/other visual arts. The background for this design is the acceleration of virtual technology which makes artistic activities undergo a transformation from a reality space to a virtual space. Digital art exhibitions are growing, with the support of various website and smartphone-based application platforms. This phenomenon is the basis for conducting research related to the Design of Digital Kultur as a 3D Website-Based Exhibition Space for Visual Art Works. The research methodology used is qualitative experimental, by developing Digital Kultur applications into digital interactive art spaces. The research results show that Digital Kultur as a virtual space that can hold visual art exhibitions is designed to have various features that make it easier for artists and audiences to access and enjoy exhibitions just like in a real gallery or exhibition space. This design is not only related to feature development, but also pays attention to the process of interaction between artists and audiences, so that the reality of the exhibition space for works of art can be fully felt even in a virtual space.